2023
DOI: 10.7759/cureus.40878
|View full text |Cite
|
Sign up to set email alerts
|

Common Side Effects of Pfizer COVID-19 Vaccine: An Experience From Pakistan

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic spread quickly. Vaccines are now being distributed to stop the infectious spread and halt fatalities. The Pfizer-BioNTech vaccine was the first mRNA-based vaccine introduced to boost immunity against COVID-19; however, it could lead to various adverse reactions. Therefore, the aim of this study was to assess the prevalence of Pfizer vaccine side effects among participants. MethodsThis was a multicenter cross-sectional study that was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…The Pfizer brand of the vaccine showed the highest frequency of people with swelling at the injection site, followed by the AstraZeneca brand with Johnson Johnson with the last frequency. This agrees with previous reports of Safi-Haider et al, (2023); Kant et al, (2021) which indicated more adverse events following the administration of Pfizer and AstraZeneca COVID-19 vaccines. Furthermore, this study observed that some adverse events were significantly dependent on gender, this agrees with the previous findings that showed females reporting more adverse events Safi-Haider et al, (2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Pfizer brand of the vaccine showed the highest frequency of people with swelling at the injection site, followed by the AstraZeneca brand with Johnson Johnson with the last frequency. This agrees with previous reports of Safi-Haider et al, (2023); Kant et al, (2021) which indicated more adverse events following the administration of Pfizer and AstraZeneca COVID-19 vaccines. Furthermore, this study observed that some adverse events were significantly dependent on gender, this agrees with the previous findings that showed females reporting more adverse events Safi-Haider et al, (2023).…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with previous reports of Safi-Haider et al, (2023); Kant et al, (2021) which indicated more adverse events following the administration of Pfizer and AstraZeneca COVID-19 vaccines. Furthermore, this study observed that some adverse events were significantly dependent on gender, this agrees with the previous findings that showed females reporting more adverse events Safi-Haider et al, (2023). In this study, one (1) individual reported fainting after receiving the Moderna vaccine, whereas three (3) reported fainting after receiving the AstraZeneca vaccine, although few studies have shown that fainting is a rare adverse event following immunization (Alemayehu et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Pain at the injection site, fever, headache, fatigue, and muscle and joint pain were the common side effects. Intriguingly, females perceived more side effects compared with males, and subjects under sixty were more likely to experience side effects than the participants in other age groups [ 6 ]. When monitoring adverse events following immunization (AEFI) with four COVID-19 vaccines (AstraZeneca, Pfizer, Moderna, and Novavax) across a four-dose schedule (primary doses 1, 2, and 3, and booster), the Moderna vaccinations were associated with higher proportions of AEFI compared with the others.…”
mentioning
confidence: 99%